A 10‐year prediagnostic follow‐up study shows that serum RNA signals are highly dynamic in lung carcinogenesis. Issue 2 (10th January 2020) - Umu, Sinan Uğur; Langseth, Hilde; Keller, Andreas; Meese, Eckart; Helland, Åslaug; Lyle, Robert; Rounge, Trine B.
Abstract : The majority of lung cancer (LC) patients are diagnosed at a late stage, and survival is poor. Circulating RNA molecules are known to have a role in cancer; however, their involvement before diagnosis remains an open question. In this study, we investigated circulating RNA dynamics in prediagnostic LC samples, focusing on smokers, to identify if and when disease‐related signals can be detected in serum. We sequenced small RNAs in 542 serum LC samples donated up to 10 years before diagnosis and 519 matched cancer‐free controls coming from 905 individuals in the Janus Serum Bank. This sample size provided sufficient statistical power to independently analyze time to diagnosis, stage, and histology. The results showed dynamic changes in differentially expressed circulating RNAs specific to LC histology and stage. The greatest number of differentially expressed RNAs was identified around 7 years before diagnosis for early‐stage LC and 1–4 years prior to diagnosis for locally advanced and advanced‐stage LC, regardless of LC histology. Furthermore, NSCLC and SCLC histologies have distinct prediagnostic signals. The majority of differentially expressed RNAs were associated with cancer‐related pathways. The dynamic RNA signals pinpointed different phases of tumor development over time. Stage‐specific RNA profiles may be associated with tumor aggressiveness. Our results improve the molecular understanding of carcinogenesis. They indicate substantial opportunity for screening and improved treatment and will guide further research on early detection of LC. However, the dynamic nature of the RNA signals also suggests challenges for prediagnostic biomarker discovery. Abstract : We investigated circulating RNA dynamics in prediagnostic lung cancer (LC) samples, focusing on smokers, to identify if and when disease‐related signals can be detected in serum. The results showed dynamic changes in differentially expressed circulating RNAs specific to LC histology and stage. The dynamic RNA signals identified different phases of tumor development over time and were associated with cancer‐related pathways.